Perbandingan Ektrak Konvensional dengan Green Ektraksi Umbi Porang (Amorphophallus Muelleri) terhadap Aktivitas Antioksidan - Pasti Marito Samosir; Roy Indrianto Bangar; Vera Estefania Kaban (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Porang tuber (Amorphophallus muelleri) contains various bioactive compounds with potential antioxidant activity, while extraction efficiency is strongly influenced by the applied method. This study aimed to compare conventional and environmentally friendly extraction techniques, including maceration, Soxhlet extraction, Microwave-Assisted Extraction (MAE), and Ultrasonic-Assisted Extraction (UAE), using 70% ethanol as the solvent. Antioxidant activity was evaluated using the DPPH radical scavenging assay and expressed as IC₅₀ values. The results showed that differences in extraction methods significantly affected antioxidant activity. Soxhlet extraction exhibited the highest antioxidant activity with the lowest IC₅₀ value (0.1788 µg/mL), followed by MAE (0.4312 µg/mL), maceration (0.6315 µg/mL), and UAE (0.6574 µg/mL). The superiority of the Soxhlet method is related to continuous solvent reflux and heat-assisted mass transfer, which enhance the release of antioxidant compounds. These findings confirm that porang tuber is a promising natural antioxidant source, with Soxhlet extraction identified as the most effective method under the applied experimental conditions for future development of functional food, nutraceutical, and pharmaceutical applications.